Phosphate inorganic intumescent flame-retardant coating for transformer substation or converter station as well as preparation method and application thereof
By combining glass powder with different melting points and inorganic flame retardant, and combining silane coupling agent to modify it, the modified glass powder is formed, which solves the problem of insufficient high temperature resistance of phosphate coatings, and achieves temperature resistance and environmental protection above 1200℃ nature.
Patent Information
- Application Number
- CN202411576428.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-11-06
AI Technical Summary
The high-temperature resistance of existing phosphate coatings is insufficient, making it difficult to maintain stable performance in high-temperature environments.
By combining glass powder with a melting point of 500°C, glass powder with a melting point of 700°C and glass powder with a melting point of 350°C, and modified with a silane coupling agent to form a modified glass powder and combine it with an inorganic flame retardant and a curing agent. The melt foaming theory is used to generate a carbon layer to improve the high temperature resistance of the coating.
The temperature resistance performance above 1200℃ is achieved, the coating can maintain fire resistance for more than 60 minutes, and the curing process is simplified, the use of chromium elements is avoided, and environmental protection is improved.
Smart Images

Figure CN119220116A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of high temperature resistant coatings, and in particular to a phosphate inorganic expanding flame retardant coating for a transformer substation or a converter station, and a preparation method and application thereof. Background Art
[0002] High temperature resistant coatings usually refer to coatings that can be used in environments above 200°C, and the coatings do not undergo significant performance changes, the color remains basically the same, and the film layer does not have defects such as cracks. In short, coatings that can maintain their physical and mechanical properties at a stable level are called high temperature resistant coatings. my country's substations (converter stations) are distributed in many locations, many of which are in harsh environments, and require good stability for flame retardant coatings. High temperature resistant coatings are widely used and promoted due to their good performance at high temperatures. They are widely used in petroleum cracking equipment, chimneys, high temperature furnaces, heat exchangers, engines and their exhaust pipes, high temperature steam pipes, etc. With the development of the global aviation and aerospace industries, people are paying more and more attention to high temperature resistant coatings, and this type of coating will be promoted to more industries and application fields.
[0003] Phosphate coatings are a type of coating that uses water-soluble phosphates as coating binders and metal oxides as phosphate curing agents. The pigments and fillers of the coatings are mainly inorganic high-temperature resistant fillers, and the curing agents are mainly metal oxides. Compared with organic coatings that use organic polymers as binders, inorganic coatings that use high-temperature resistant phosphate binders have the advantages of good heat resistance and resistance to high-temperature oxidation. Generally, organic polymers have poor heat resistance and cannot be used at high temperatures for a long time. When the phosphate coating is cured after coating, a high-temperature resistant coating can be formed on the surface of the material. The coating system can withstand high-temperature airflow erosion and can traditionally withstand high temperatures of 650°C.
[0004] The Chinese patent application document with publication number CN112266633A discloses a fire retardant coating resistant to high temperature of 1700℃ and its preparation method. A fire retardant coating that can be maintained at 1700℃ for 20 minutes is prepared by using aluminum hydroxide, silicon dioxide, mica powder, magnesium oxide, double rare earth tantalate and basalt fiber, effectively filling the gap of domestic high temperature resistant coatings. The Chinese patent application document with publication number CN115093725A discloses a fire retardant coating composed of aluminum dihydrogen phosphate, zinc oxide, cerium oxide, gadolinium zirconate, polysiloxane, zirconium boride, pick powder, tungsten powder, short-cut high silica fiber, chromium trioxide, potassium chromate, non-silicon defoamer and deionized water, which can withstand 1800℃. The temperature resistance of existing phosphate coatings is mainly achieved by the synergistic effect of compounding high temperature resistant inorganic fillers. Intumescent fire retardant coating is a functional coating that is applied on the surface of the substrate and reacts to form a carbon layer much thicker than the original coating when exposed to fire, thereby reducing the heat conduction to the substrate and improving the fire resistance limit of the protected substrate. At present, intumescent flame retardant coatings mainly achieve the effect of carbon layer expansion through intumescent flame retardants composed of acid source, carbon source and gas source, and are rarely used in phosphate flame retardant coatings.
[0005] The Chinese patent application document with publication number CN115418121A discloses an iron-based water-based high-temperature resistant insulating coating, a preparation method and an application thereof. The coating is composed of the following components: 30 to 50 parts of low-melting point glass powder, 5 to 20 parts of inorganic aggregate, 0.5 to 5 parts of binder, 0.2 to 5 parts of dispersant, 0 to 5 parts of organic silicon film-forming aid, 0.5 to 5 parts of silica sol, and 35 to 60 parts of deionized water. The low melting point glass powder is LX-45, GT-50 and LX-680; or, the low melting point glass powder is LX-45, TY-906 and G-57; or, the low melting point glass powder is LX-45, TY-280, G-57 and LX-680; the initial melting temperature of the low melting point glass powder is 420°C to 600°C; it only uses water as a dispersion medium and does not contain volatile solvents, the preparation method is green and environmentally friendly, the sintering temperature is low (540 to 620°C), the damage to the substrate is small, the organic components are small, and the problems of coating powdering, decreased adhesion, coating shedding, etc. caused by the decomposition of organic matter at high temperature are avoided, but its high temperature resistance is still not very ideal, and the curing is divided into three temperature stages, and the curing procedure is relatively complicated. Summary of the invention
[0006] The technical problem to be solved by the present invention is how to improve the high temperature resistance of phosphate coating.
[0007] The present invention solves the above technical problems through the following technical means:
[0008] A phosphate inorganic intumescent flame-retardant coating for a substation or a converter station, wherein the raw materials thereof include, by weight: 30-50 parts of phosphate, 10-20 parts of modified glass powder, 5-20 parts of inorganic flame retardant, 3-20 parts of filler, 5-10 parts of curing agent, and 3-10 parts of auxiliary agent;
[0009] The modified glass powder is prepared by mixing one or both of glass powder with a melting point of 500° C. and glass powder with a melting point of 700° C. with glass powder with a melting point of 350° C. and then modifying the mixture with a silane coupling agent.
[0010] Preferably, the phosphate is aluminum dihydrogen phosphate.
[0011] Preferably, the inorganic flame retardant is a mixture of one or more of magnesium hydroxide, aluminum hydroxide, magnesium carbonate, basic magnesium carbonate, and basic copper carbonate.
[0012] Preferably, the inorganic flame retardant is a mixture of one or more of magnesium hydroxide and aluminum hydroxide.
[0013] Preferably, the filler is a mixture of one or more of nano titanium dioxide, nano aluminum oxide, silicon carbide, kaolin, mica powder and talc powder.
[0014] Preferably, the curing agent is a mixture of one or more of MgO, ZnO and CuO.
[0015] Preferably, the curing agent is MgO.
[0016] Preferably, the auxiliary agent is a defoamer, an adhesion promoter, or a mixture of both.
[0017] Preferably, the defoaming agent is defoaming agent YS-T118.
[0018] Preferably, the adhesion promoter is one of SN 6797 adhesion promoter and 5140B water-based adhesion promoter, or a mixture of the two.
[0019] Preferably, the modified glass powder is a mixture of glass powder with a melting point of 350° C., glass powder with a melting point of 500° C., and glass powder with a melting point of 700° C., which is modified by a silane coupling agent.
[0020] Preferably, the mass ratio of the glass powder with a melting point of 350° C., the glass powder with a melting point of 500° C., and the glass powder with a melting point of 700° C. is 1-2:1:1.
[0021] Preferably, the modified glass powder is a mixture of glass powder with a melting point of 350° C. and glass powder with a melting point of 500° C., which is modified by a silane coupling agent.
[0022] Preferably, the mass ratio of the glass powder with a melting point of 350° C. to the glass powder with a melting point of 500° C. is 1:1-2.
[0023] Preferably, the silane coupling agent is silane coupling agent KH570.
[0024] Preferably, the preparation process of the modified glass powder includes the following steps: grinding glass powders of different melting points according to a ratio, sieving and mixing them by ball milling, mixing them with an ethanol / water mixed solution, adding a silane coupling agent and stirring evenly, heating to react, and drying to obtain the modified glass powder.
[0025] Preferably, the mass ratio of glass powder to silane coupling agent is 5:1.
[0026] Preferably, the mixture is heated to 60° C. and the reaction is carried out for 12 hours.
[0027] Preferably, the raw material of the phosphate inorganic intumescent flame retardant coating for the substation or converter station also includes water.
[0028] Preferably, the weight ratio of phosphate to water is 4-5:5-6.
[0029] Preferably, the melting range of the glass powder matches the temperature range of the gas generated by thermal decomposition of the inorganic flame retardant.
[0030] Preferably, the pyrolysis temperature range of the inorganic flame retardant is consistent with the melting point range of the glass powder raw material; for example, magnesium hydroxide begins to decompose at 300°C, generates H2O (gas) at 350°C, and ends decomposition at 480°C; which is consistent with the melting point range of the glass powder with 350°C as the starting melting point and 463°C as the half melting point. The temperature of the generated gas is consistent with the temperature range where the glass powder begins to melt, and the entire thermal decomposition process covers most of the glass powder melting range, which can play a role in gas expansion when the glass powder melts and flows, promoting the melting and flow of the glass powder to form a secondary film in the high temperature zone. The thermal decomposition of magnesium hydroxide absorbs heat, which improves the high temperature resistance of the coating. At the same time, the generated MgO can achieve the effect of secondary curing of aluminum dihydrogen phosphate in the high temperature zone.
[0031] In the present invention, the initial melting temperature of the glass powder is adjusted to 350-700°C by compounding glass powder, and the melting range of 350-500°C in the compounded glass powder is utilized to preferably design an inorganic flame retardant to achieve the effect of heat resistance of carbon layer expansion in the low temperature zone (350-500°C). The initial melting components of 500-700°C in the compounded glass powder are utilized to achieve secondary film formation in the high temperature zone (500-700°C), thereby compensating for the problem of mismatch between the thermal expansion coefficient of the high-temperature phosphate inorganic film-forming agent and the substrate, and ultimately achieving the purpose of temperature resistance of 1200°C.
[0032] The present invention also proposes a method for preparing the phosphate inorganic intumescent flame-retardant coating for a substation or a converter station, comprising the following steps:
[0033] S1. Grinding, sieving, and ball-milling the modified glass powder, inorganic flame retardant, and filler to obtain a composite filler;
[0034] S2, prepare a phosphate aqueous solution, add the composite filler and additives in S1, and heat and stir;
[0035] S3. Add a curing agent to the product in S2 and stir to obtain the phosphate inorganic expanding flame retardant coating for the substation or converter station.
[0036] Preferably, the mass concentration of the phosphate aqueous solution is 40-50%.
[0037] The present invention also proposes an application of the phosphate inorganic expanding flame retardant coating for a transformer substation or a converter station in the transformer substation or the converter station.
[0038] The present invention also provides a coating, which is prepared by using the phosphate inorganic expansion flame retardant coating for transformer substation or converter station.
[0039] The advantages of the present invention are:
[0040] The present invention uses phosphate as a film-forming agent, based on the melt foaming theory, and prepares a phosphate inorganic expansion flame retardant coating by compounding an inorganic flame retardant and glass powder. High temperature resistant inorganic fillers can further improve the high temperature resistance of the coating. The curing agent can realize room temperature curing of the phosphate coating and improve the curing process of the coating. The addition of auxiliary defoaming agents and adhesion promoters has a certain improvement effect on the adhesion and dispersibility of the coating. Under the synergistic effect of phosphate, modified glass powder, inorganic flame retardant, high temperature resistant filler, curing agent and auxiliary agent, the present invention can effectively improve the expansion flame retardant effect and high temperature resistance of the coating.
[0041] (1) The present invention is based on the principle of intumescent flame retardant and utilizes melt foaming theory. By matching the thermal decomposition temperature of the inorganic flame retardant with the melting point of the glass powder, the inorganic flame retardant is pyrolyzed to generate gas. At this time, the low-melting point glass powder melts into liquid, and the gas expands to generate a carbon layer. In addition, the glass powders with different melting points can melt and flow at high temperatures (350-700°C) to play a secondary film-forming role. The preparation of phosphate inorganic intumescent flame-retardant coatings is achieved without using intumescent flame retardants, and the high temperature resistance of conventional phosphate coatings is improved by the intumescent carbon layer.
[0042] (2) The preparation process of the coating of the present invention is simple. The functional fillers used in the coating are fully mixed by grinding, sieving and ball milling the modified glass powder, inorganic flame retardant and high temperature resistant fillers. The phosphate aqueous solution is passed through and the temperature of the aqueous solution is controlled to allow the filler and the phosphate to fully react.
[0043] (3) The phosphate inorganic intumescent flame-retardant coating prepared by the present invention can generate an intumescent flame-retardant carbon layer when burned at 1200°C, which can play a good fire-proof role for the base material and has a heat resistance time of more than 60 minutes at 1200°C.
[0044] (4) The phosphate inorganic intumescent flame-retardant coating prepared by the present invention can be cured at room temperature, and the coating formula does not contain chromium elements, thereby improving the environmental friendliness of the phosphate inorganic intumescent flame-retardant coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 This is a back temperature test diagram of the phosphate inorganic intumescent flame retardant coating prepared in Examples 1-4 of the present invention;
[0046] Figure 2 This is a digital image of the phosphate inorganic intumescent flame retardant coating and the carbon layer prepared in Example 1 of the present invention;
[0047] Figure 3 This is a scan of the expanded carbon layer of the phosphate inorganic intumescent flame-retardant coating prepared in Example 2 of the present invention;
[0048] Figure 4 This is a back temperature test diagram of the coatings prepared in Comparative Examples 1-7 of the present invention;
[0049] Figure 5 This is a digital image of the carbon layer of the coating prepared in Comparative Example 6 of the present invention;
[0050] Figure 6 Digital image of the carbon layer of the coating obtained in Comparative Example 7 of the present invention
[0051] Figure 7 This is a digital image of the coating layer of the coating prepared in Comparative Example 9 of the present invention. DETAILED DESCRIPTION
[0052] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0053] Unless otherwise specified, the test materials and reagents used in the following examples can be obtained from commercial sources.
[0054] If no specific techniques or conditions are specified in the examples, they can be carried out according to the techniques or conditions described in the literature in the art or according to the product instructions.
[0055] In the following examples and comparative examples, the melting point of the glass powder is the temperature at which the glass powder begins to melt;
[0056] The glass powder with a melting point of 350°C is GT-35 low melting point glass powder, and the manufacturer is Anmi Micro-Nano New Materials (Guangzhou) Co., Ltd.;
[0057] The glass powder with a melting point of 500°C is GT-50 low melting point glass powder, and the manufacturer is Anmi Micro-Nano New Materials (Guangzhou) Co., Ltd.
[0058] The glass powder with a melting point of 700°C is GT-70 low-melting-point glass powder, and the manufacturer is Anmi Micro-Nano New Materials (Guangzhou) Co., Ltd.
[0059] The adhesion promoter SN 6797 comes from Foshan Keerle Building Materials Co., Ltd.
[0060] The defoaming agent YS-T118 is sourced from Beijing Kemite Technology Development Co., Ltd.
[0061] Example 1
[0062] A phosphate inorganic intumescent flame-retardant coating for a transformer substation or a converter station. The raw materials thereof include, by weight, 50 parts of aluminum dihydrogen phosphate, 10 parts of modified glass powder, 10 parts of magnesium hydroxide, 3 parts of nano-TiO2, 4 parts of nano-Al2O3, 10 parts of MgO curing agent, and 3 parts of adhesion promoter SN 6797.
[0063] The modified glass powder is prepared by compounding glass powders with melting points of 350°C, 500°C, and 700°C (the initial melting temperature of the glass powder) in a mass ratio of 1:1:1 and then modifying with silane. The specific preparation process includes the following steps:
[0064] (1) Grind glass powders with different melting points according to the ratio, sieve and mix them, and ball mill for 30 minutes;
[0065] (2) 10 parts by mass of the ball-milled glass powder was mixed with an ethanol / water mixed solution (volume ratio of ethanol: water = 8:2) at a mass fraction of 30%, and then 2 parts by mass of silane coupling agent KH570 was added, and mechanically stirred for 30 minutes to ensure that the glass powder was mixed evenly;
[0066] (3) The uniformly mixed glass powder is kept constant at 60° C., reacted for 12 hours, and freeze-dried to obtain the modified glass powder.
[0067] The preparation process of phosphate inorganic intumescent flame retardant coating is as follows:
[0068] (1) Grinding the modified glass powder, magnesium hydroxide, nano-TiO2, and nano-Al2O3 separately, sieving, and ball-milling for 30 minutes to obtain a composite filler;
[0069] (2) preparing a 50% by mass aqueous solution of aluminum dihydrogen phosphate, adding the composite filler and adhesion promoter SN 6797 in step (1), and stirring at 50° C. for 60 min;
[0070] (3) MgO was added and stirred for 5 minutes to obtain a uniformly mixed aluminum dihydrogen phosphate inorganic intumescent flame retardant coating, which was then brushed. The substrate was stainless steel and the coating thickness was 3 mm.
[0071] Example 2
[0072] A phosphate inorganic intumescent flame-retardant coating for a transformer substation or a converter station. The raw materials thereof include, by weight, 40 parts of aluminum dihydrogen phosphate, 12 parts of modified glass powder, 18 parts of magnesium hydroxide, 5 parts of nano-TiO2, 5 parts of nano-Al2O3, 8 parts of talcum powder, 8 parts of ZnO curing agent, 2 parts of adhesion promoter SN 6797, and 2 parts of defoaming agent YS-T118.
[0073] The modified glass powder is prepared by compounding glass powders with melting points of 350° C. and 500° C. (initial melting temperature of the glass powder) at a mass ratio of 1:2 and then modifying with silane. The specific preparation process is the same as that of Example 1.
[0074] The preparation process of phosphate inorganic intumescent flame retardant coating is as follows:
[0075] (1) Grinding modified glass powder, magnesium hydroxide, nano titanium dioxide, nano aluminum oxide, and talc powder separately, sieving, and ball milling for 30 minutes to obtain a composite filler;
[0076] (2) preparing a 40% by mass aqueous solution of aluminum dihydrogen phosphate, adding the composite filler, adhesion promoter SN 6797 and defoamer YS-T118 prepared in step (1), and stirring at 50° C. for 60 min;
[0077] (3) Add ZnO and stir for 5 minutes to obtain a uniformly mixed aluminum dihydrogen phosphate inorganic intumescent flame retardant coating, which is then brushed. The substrate is stainless steel and the coating thickness is 3 mm.
[0078] Example 3
[0079] A phosphate inorganic intumescent flame-retardant coating for a transformer substation or a converter station. The raw materials thereof include, by weight, 45 parts of aluminum dihydrogen phosphate, 10 parts of modified glass powder, 15 parts of magnesium hydroxide, 6 parts of nano titanium dioxide, 6 parts of talc powder, 6 parts of silicon carbide, 8 parts of ZnO curing agent, 2 parts of adhesion promoter SN 6797, and 2 parts of defoaming agent YS-T118.
[0080] The modified glass powder is prepared by mixing glass powders with melting points of 350° C. and 500° C. in a mass ratio of 1:1 and then modifying with silane. The specific preparation process is the same as that of Example 1.
[0081] The preparation process of phosphate inorganic intumescent flame retardant coating is as follows:
[0082] (1) Grinding modified glass powder, magnesium hydroxide, nano titanium dioxide, talc powder, and silicon carbide separately, sieving, and ball milling for 30 minutes to obtain a composite filler;
[0083] (2) preparing a 45% by mass aqueous solution of aluminum dihydrogen phosphate, adding the composite filler, adhesion promoter SN 6797 and defoamer YS-T118 prepared in step (1), and stirring at 50° C. for 60 min;
[0084] (3) Add ZnO and stir for 5 minutes to obtain a uniformly mixed aluminum dihydrogen phosphate inorganic intumescent flame retardant coating, which is then brushed. The substrate is stainless steel and the coating thickness is 3.5 mm.
[0085] Example 4
[0086] A phosphate inorganic intumescent flame-retardant coating for a transformer substation or a converter station. The raw materials thereof include, by weight, 35 parts of aluminum dihydrogen phosphate, 15 parts of modified glass powder, 20 parts of magnesium hydroxide, 7 parts of nano-TiO2, 5 parts of talc, 5 parts of kaolin, 6 parts of MgO curing agent, 3 parts of adhesion promoter SN 6797, and 2 parts of defoaming agent YS-T118.
[0087] The modified glass powder is prepared by compounding glass powders with melting points of 350° C., 500° C. and 700° C. in a mass ratio of 2:1:1 and then modifying with silane. The specific preparation process is the same as that of Example 1.
[0088] The preparation process of phosphate inorganic intumescent flame retardant coating is as follows:
[0089] (1) Grinding the modified glass powder, magnesium hydroxide, nano titanium dioxide, talc, and kaolin separately, sieving, and ball milling for 30 minutes to obtain a composite filler;
[0090] (2) preparing a 35% by mass aqueous solution of aluminum dihydrogen phosphate, adding the composite filler, adhesion promoter SN 6797 and defoamer YS-T118 prepared in step (1), and stirring at 50° C. for 60 min;
[0091] (3) MgO was added and stirred for 5 minutes to obtain a uniformly mixed aluminum dihydrogen phosphate inorganic intumescent flame retardant coating, which was then brushed. The substrate was stainless steel and the coating thickness was 4 mm.
[0092] Comparative Example 1
[0093] The only difference from Example 1 is that the raw materials do not contain modified glass powder. The raw materials include 50 parts of aluminum dihydrogen phosphate, 20 parts of magnesium hydroxide, 3 parts of nano-TiO2, 4 parts of nano-Al2O3, 10 parts of MgO curing agent, and 3 parts of adhesion promoter SN 6797 in parts by mass.
[0094] According to the preparation process of the inorganic phosphate intumescent flame retardant coating in Example 1, the modified glass powder is correspondingly deleted to obtain a uniformly mixed aluminum dihydrogen phosphate inorganic intumescent flame retardant coating, and the coating is applied by brushing. The substrate is stainless steel, and the coating thickness is 3 mm.
[0095] Comparative Example 2
[0096] The only difference from Example 1 is that the raw materials do not contain magnesium hydroxide. The raw materials include 50 parts of aluminum dihydrogen phosphate, 20 parts of modified glass powder, 3 parts of nano-TiO2, 4 parts of nano-Al2O3, 10 parts of MgO curing agent, and 3 parts of adhesion promoter SN 6797 in parts by mass.
[0097] The remaining steps and preparation methods are consistent with those in Example 1 (magnesium hydroxide is deleted accordingly), and a uniformly mixed aluminum dihydrogen phosphate inorganic intumescent flame retardant coating is obtained, and the coating is brushed. The substrate is stainless steel, and the coating thickness is 3 mm.
[0098] Comparative Example 3
[0099] The difference from Example 1 is that the glass powder is a glass powder with a single melting point, that is, the glass powder with a melting point of 350°C is used to replace the glass powders with melting points of 350°C, 500°C, and 700°C in a mass ratio of 1:1:1 in Example 1, and the remaining steps are consistent with Example 1.
[0100] Comparative Example 4
[0101] The difference from Example 1 is that the glass powder is a glass powder with a single melting point, that is, the glass powder with a melting point of 500°C is used to replace the glass powders with melting points of 350°C, 500°C, and 700°C in the mass ratio of 1:1:1 in Example 1, and the remaining steps are consistent with Example 1.
[0102] Comparative Example 5
[0103] The difference from Example 1 is that the glass powder is a glass powder with a single melting point, that is, the glass powder with a melting point of 700°C is used to replace the glass powders with melting points of 350°C, 500°C, and 700°C in the mass ratio of 1:1:1 in Example 1, and the remaining steps are consistent with Example 1.
[0104] Comparative Example 6
[0105] The only difference from Example 1 is that in the preparation process of the modified glass powder, the glass powder after ball milling is directly freeze-dried, and the reaction process of step (2) and step (3) is not carried out. Experimental phenomenon: The glass powder agglomerates and has poor dispersibility.
[0106] Comparative Example 7
[0107] The difference from Example 1 is that the glass powder compounding ratio is different. Glass powders with melting points of 500°C and 700°C in a mass ratio of 1:1 are used to replace the glass powders with melting points of 350°C, 500°C and 700°C in a mass ratio of 1:1:1 in Example 1, and the remaining steps are the same as Example 1.
[0108] Comparative Example 8
[0109] The difference from Example 4 is that the ratio of aluminum dihydrogen phosphate, modified glass powder and magnesium hydroxide is different. The raw materials include 60 parts of aluminum dihydrogen phosphate, 15 parts of modified glass powder, 20 parts of magnesium hydroxide, 7 parts of nano-TiO2, 5 parts of talc, 5 parts of kaolin, 6 parts of MgO curing agent, 3 parts of adhesion promoter SN 6797, 2 parts of defoaming agent YS-T118, and the remaining steps are consistent with Example 4.
[0110] Comparative Example 9
[0111] The difference from Example 4 is that the ratio of aluminum dihydrogen phosphate, modified glass powder and magnesium hydroxide is different. The raw materials include 25 parts of aluminum dihydrogen phosphate, 15 parts of modified glass powder, 20 parts of magnesium hydroxide, 7 parts of nano-TiO2, 5 parts of talc, 5 parts of kaolin, 6 parts of MgO curing agent, 3 parts of adhesion promoter SN 6797, and 2 parts of defoaming agent YS-T118 in terms of mass parts. The remaining steps are consistent with Example 4.
[0112] The phosphate inorganic intumescent flame retardant coatings obtained in Examples 1-4 were compared with the phosphate coatings obtained in Comparative Examples 1-8. An acetylene burner was used to provide a stable fire source of 1200°C. The coatings were applied to a stainless steel substrate. A thermocouple was used to record the back temperature of the plate after burning the twelve coatings at 1200°C for 30-60 minutes (burning for 30 minutes, the final stable temperature was higher than 300°C, and no more burning occurred). The relevant data obtained are shown in Tables 1 and 2. Figure 1-Figure 6 shown.
[0113] Table 1 Back surface temperature of twelve phosphate coatings
[0114]
[0115] From Table 1 and Figure 1-6It can be seen that the carbon layer of the aluminum dihydrogen phosphate coating with modified glass powder and inorganic flame retardant expanded, and the back temperature was significantly lower than that of the control. In the range of 300-500℃, the inorganic flame retardant pyrolyzes to generate a large amount of gas, and the low-melting point glass powder melts and flows, and the carbon layer expands under the action of the gas; the compounded glass powder melts and forms a secondary film in different temperature ranges to repair the cracks generated when the aluminum dihydrogen phosphate is filled at high temperature; after the high-temperature resistant filler is refined, the density of the coating matrix in the high-temperature range is improved, and the high-temperature resistance of the coating is improved.
[0116] Figure 1 The back temperature test diagram of the aluminum dihydrogen phosphate inorganic intumescent flame retardant coating prepared in Examples 1-4. The back temperature curve represents the back temperature at the center of the coating exposed to fire. The central stable temperature of the back of the coating in Examples 1-4 was all below 300°C.
[0117] Figure 2 The digital images are before and after the burning test of the aluminum dihydrogen phosphate inorganic intumescent flame retardant coating prepared in Example 1. The surface of the coating is dense without obvious cracks, and the carbon layer expands with air after burning, and the carbon layer still maintains structural integrity without slagging.
[0118] Figure 3 This is a scan of the expanded carbon layer of the aluminum dihydrogen phosphate inorganic intumescent flame retardant coating prepared in Example 2. The macroscopic carbon layer of the coating is expanded, and the microscopic morphology of the carbon layer is porous.
[0119] Figure 4The back temperature test diagram of the coatings prepared in Comparative Examples 1-7. The blank sample is the back temperature of the substrate without coating. The back temperature results of Comparative Examples 1-7 are shown in Table 1. In Comparative Example 1, since no modified glass powder was added, Mg(OH)2 pyrolyzed to produce gas, and the carbon layer expanded, but the high-temperature film-forming adhesion of aluminum dihydrogen phosphate decreased, and the high-temperature resistance of the coating was worse than that of Example 1. In Comparative Example 2, since no Mg(OH)2 gas generating agent was added, the carbon layer of the coating had a low expansion multiple, and the high-temperature resistance and heat insulation performance were worse than those of Example 1. In Comparative Examples 3-5, the glass powder has a single melting point, and the glass powder has a certain high-temperature film-forming effect after melting and flowing, and the heat insulation effect is better. When the melting point of the glass powder is 350°C, the glass powder melts too quickly, the coating melts through and cracks, and the high temperature resistance of the coating is lower than that of Example 1; when the melting point of the glass powder is 500°C, the starting temperature of the glass powder melt flow fails to cover the gasification decomposition process of Mg(OH)2, resulting in cracks in the coating; when the melting point of the glass powder is 700°C, the temperature of the glass powder melt flow is too high, and it does not play a role in secondary film formation in the high temperature zone and supplement the mismatch between the thermal expansion coefficient of the aluminum dihydrogen phosphate film-forming agent and the metal substrate. Therefore, the temperature resistance of the coating containing glass powder with a single melting point is worse than that of the compound glass powder. In Comparative Example 6, the compounded glass powder was not modified with silane, and the coating had better high temperature resistance, but the dispersibility of the compounded glass powder was poor, which also resulted in the coating having poor high temperature resistance and heat insulation performance compared with Example 1; in Comparative Example 7, only glass powders with melting points of 500°C and 700°C were compounded. Since the melting range of the glass powder did not match the temperature range of the gas generated by the thermal decomposition of the inorganic flame retardant, the carbon layer of the coating had a low expansion multiple, poor high temperature resistance and heat insulation performance compared with Example 1, and cracks appeared in the coating. In Comparative Example 8, the content of aluminum dihydrogen phosphate film-forming agent was increased, the ratio of glass powder to inorganic flame retardant was relatively reduced, and the flame retardant expansion effect was reduced; in Comparative Example 9, the content of aluminum dihydrogen phosphate film-forming agent was reduced, the coating had poor coating effect, the coating slag fell off, and it was difficult to form a film.
[0120] Figure 5 The carbon layer of the phosphate inorganic coating prepared in Comparative Example 6 has an incomplete appearance and poor secondary film-forming effect at high temperature due to poor dispersion of the glass powder.
[0121] Figure 6 The carbon layer of the phosphate inorganic flame retardant coating prepared in Comparative Example 7 has poor secondary film-forming effect of the carbon layer of the coating due to the mismatch between the characteristic temperatures of the glass powder and the inorganic flame retardant, and cracks appear in the carbon layer.
[0122] Figure 7 The coating of the phosphate inorganic coating prepared in Comparative Example 9 has poor film-forming properties due to the low proportion of film-forming agent, resulting in the coating falling off.
[0123] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A phosphate inorganic intumescent flame retardant coating for a substation or a converter station, characterized in that: The raw materials include, by weight: 30-50 parts of phosphate, 10-20 parts of modified glass powder, 5-20 parts of inorganic flame retardant, 3-20 parts of filler, 5-10 parts of curing agent, and 3-10 parts of auxiliary agent; The modified glass powder is prepared by mixing one or both of glass powder with a melting point of 500° C. and glass powder with a melting point of 700° C. with glass powder with a melting point of 350° C. and then modifying the mixture with a silane coupling agent.
2. The phosphate inorganic intumescent flame-retardant coating for a transformer substation or a converter station according to claim 1, characterized in that: The phosphate is aluminum dihydrogen phosphate.
3. The phosphate inorganic intumescent flame-retardant coating for a transformer substation or a converter station according to claim 1, characterized in that: The inorganic flame retardant is a mixture of one or more of magnesium hydroxide, aluminum hydroxide, magnesium carbonate, basic magnesium carbonate, and basic copper carbonate.
4. The phosphate inorganic intumescent flame-retardant coating for a transformer substation or a converter station according to claim 1, characterized in that: The filler is a mixture of one or more of nano titanium dioxide, nano aluminum oxide, silicon carbide, kaolin, mica powder and talcum powder.
5. The phosphate inorganic intumescent flame-retardant coating for a transformer substation or a converter station according to claim 1, characterized in that: The curing agent is a mixture of one or more of MgO, ZnO and CuO.
6. The phosphate inorganic intumescent flame-retardant coating for a transformer substation or a converter station according to claim 1, characterized in that: The auxiliary agent is one of a defoamer and an adhesion promoter or a mixture of both.
7. The phosphate inorganic intumescent flame-retardant coating for a transformer substation or a converter station according to claim 6, characterized in that: The defoamer is defoamer YS-T118.
8. The phosphate inorganic intumescent flame-retardant coating for a transformer substation or a converter station according to claim 6, characterized in that: The adhesion promoter is one of SN 6797 adhesion promoter and 5140B water-based adhesion promoter or a mixture of the two.
9. The phosphate inorganic intumescent flame-retardant coating for a transformer substation or a converter station according to claim 1, characterized in that: The modified glass powder is obtained by mixing glass powder with a melting point of 350° C., glass powder with a melting point of 500° C., and glass powder with a melting point of 700° C. and then modifying the mixture with a silane coupling agent.
10. The phosphate inorganic intumescent flame retardant coating for a transformer substation or a converter station according to claim 9, characterized in that: The mass ratio of the glass powder with a melting point of 350°C, the glass powder with a melting point of 500°C, and the glass powder with a melting point of 700°C is 1-2:1:
1.
11. The phosphate inorganic intumescent flame-retardant coating for a transformer substation or a converter station according to claim 1, characterized in that: The modified glass powder is obtained by mixing glass powder with a melting point of 350° C. and glass powder with a melting point of 500° C. and then modifying the mixture with a silane coupling agent.
12. The phosphate inorganic intumescent flame retardant coating for a transformer substation or a converter station according to claim 11, characterized in that: The mass ratio of the glass powder with a melting point of 350°C to the glass powder with a melting point of 500°C is 1:1-2.
13. The phosphate inorganic intumescent flame-retardant coating for a transformer substation or a converter station according to claim 1, characterized in that: The silane coupling agent is silane coupling agent KH570.
14. The phosphate inorganic intumescent flame retardant coating for a transformer substation or a converter station according to claim 1, characterized in that: The preparation process of the modified glass powder includes the following steps: grinding glass powders with different melting points according to a ratio, sieving and mixing them by ball milling, mixing them with an ethanol / water mixed solution, adding a silane coupling agent and stirring them evenly, heating to react, and drying to obtain the modified glass powder.
15. The phosphate inorganic intumescent flame retardant coating for a transformer substation or a converter station according to claim 14, characterized in that: The mass ratio of glass powder to silane coupling agent is 5:
1.
16. The phosphate inorganic intumescent flame retardant coating for a transformer substation or a converter station according to claim 14, characterized in that: The mixture was heated to 60°C and reacted for 12 hours.
17. A method for preparing a phosphate inorganic intumescent flame-retardant coating for a transformer substation or a converter station according to any one of claims 1 to 16, characterized in that: The following steps are involved: S1. Grinding, sieving, and ball-milling the modified glass powder, inorganic flame retardant, and filler to obtain a composite filler; S2, prepare a phosphate aqueous solution, add the composite filler and additives in S1, and heat and stir; S3. Add a curing agent to the product in S2 and stir to obtain the phosphate inorganic expanding flame retardant coating for the substation or converter station.
18. The method for preparing the phosphate inorganic intumescent flame-retardant coating for a transformer substation or a converter station according to claim 17, characterized in that: The mass concentration of the phosphate aqueous solution is 40-50%.
19. Use of the phosphate inorganic intumescent flame-retardant coating for a transformer substation or a converter station as claimed in any one of claims 1 to 16 in a transformer substation or a converter station.
20. A coating, characterized in that: The invention is prepared by using the phosphate inorganic expanding flame retardant coating for a transformer substation or a converter station as described in any one of claims 1 to 16.
Citation Information
Patent Citations
Flame retardant coating layer and preparation method thereof
CN105694543A
1800 DEG C-resistant phosphate heat-insulation fireproof coating and preparation method thereof
CN115093725A
Inorganic low-temperature ceramic coating as well as preparation method and application thereof
CN115558317A
Environment-friendly, flame-retardant, high-temperature-resistant and heat-insulating composite coating for parts and preparation method
CN117551371A
Phosphate coating resistant to 1,800 degrees celsius for heat insulation and fireproofing and preparation method thereof
US20230416564A1
Cited By
Efficient flame-retardant self-repairing coating and preparation method thereof
CN119931477A
Highly efficient flame-retardant self-healing coating and preparation method thereof
CN119931477B